Middle East Pillars or Regional Opponents? The Sport Interactions of Iran and Saudi Arabia - Mahdi Shariati Feizabadi; Sadegh Ranjbar; Amir hosein Monazami (Research in Sport Management and Marketing)
Purpose: The attempts made by Saudi Arabia to utilize the soft power of sports over the last decade have helped it envision a promising post-oil future. This study aims to explain the paradigm governing the expansion of sports interactions between Iran and Saudi Arabia. Methods: The statistical population consisted of 11 political science and sports science professionals with written work (e.g., papers, books, notes, or interviews) on public diplomacy, sports diplomacy, and diplomatic interactions in the Middle East, especially between Iran and Saudi Arabia. Sampling was performed through purposive (snowball) sampling and the Delphi method until theoretical saturation. The validity and reliability of this research were evaluated with the contribution of interviewees with Intra-subject agreement of two coders. Results: The research findings indicated that four indirect categories (i.e., geopolitical, ideological, economic, and sociocultural categories) and three direct categories (i.e., sports events, human capital, and sports economy) constituted the paradigm governing the diplomatic interactions between Iran and Saudi Arabia. The key components of indirect and direct categories were economic concepts with a mean of 4.17 and sports economy with a mean of 4.30, respectively. Conclusion: According to the research findings, since Saudi Arabia has put substantial effort into organizing sports events and paid special attention to this area over the last decade, sports can be considered an intriguing means for these two countries to expand their political and economic convergence in the future.